A dynamic object tracking system of industrial robots based on visual servoing technology - Yichao MAO; Qi LU (智能科学与技术学报)
Visual servoing technology has high potential in many industrial applications.Conventionally,precise servoing is often achieved by using high-resolution cameras which are usually costly and unaffordable in many of industrial scenarios.A novel visual servoing control scheme which generates robot control signal based on the fusion of visual feedback and robot motion feedback was presented in the paper.By doing so,the robot control loop runs at a frequency independent to the visual feedback frequency (i.e.the frame rate of a camera).Therefore,it becomes feasible to achieve precise and dynamic servoing even with a low frame rate and low-cost camera.The new visual servoing scheme was introduced briefly.The feasibility of the scheme as well as its performances in low frame rate conditions was also illustrated experimentally.